Novel Effects of Combination Therapy Through Inhibition of Caspase-1/Gasdermin D Induced-Pyroptosis in Lupus Nephritis - Cao, Heng; Liang, Junyu; Liu, Jing; He, Ye; Ke, Yini; Sun, Yiduo; Jiang, Song; Lin, Jin (Frontiers in Immunology, 2021)
Objectives: Combination therapy with mycophenolate mofetil, tacrolimus and steroids are effective in achieving complete remission in lupus nephritis (LN). Combination therapy uniquely downregulated caspase-1 compared with monotherapies, which can cleave gasdermin D (GSDMD) and was recently identified as the pyroptosis executioner. We therefore investigated whether combination therapy enabled the suppression of caspase-1/GSDMD-mediated pyroptosis in LN. Methods: Expression and activation of GSDMD were detected in kidney specimens of the human and mouse with LN using immunohistochemical staining and immunoblotting. Primary podocytes isolated from MRL/lpr mice were incubated with LPS+ATP, and pretreated with monotherapy or combination therapy. Inhibition of caspase-1/GSDMD-induced pyroptosis by combination therapy were assessed in MRL/lpr mice and human specimens. Pyroptosis was examined using a FAM caspase-1 kit and flow cytometry. The correlation between pyroptosis in peripheral blood and the systemic lupus erythematosus disease activity index (SLEDAI) was analyzed. Results: Kidney tissue specimens from LN patients and mice exhibited greatly increased expression levels and cleavage of GSDMD. In cultured podocytes, combination treatment significantly suppressed the activation of NLRP3 and caspase-1 and reduced GSDMD N-terminal levels. Combination therapy repressed disease progression through inhibition of caspase-1/GSDMD-mediated pyroptosis in both humans and MRL/lpr mice. Caspase-1/PI positive cell numbers in peripheral blood were positively correlated with SLE-DAI. LN patients with complete remission and partial remission had remarkably reduced caspase-1/PI positive cell numbers compared to baseline. Ac-FLTD-CMK, a GSDMD-derived inhibitor, prevented the development of LN. Conclusion: Combination therapy suppressed caspase-1/GSDMD-mediated pyroptosis in vitro and in vivo and reduced disease progression.